Outsourcing war : the just war tradition in the age of military privatization - Eckert, Amy (Cornell University Press, 2016)
Recent decades have seen an increasing reliance on private military contractors (PMCs) to provide logistical services, training, maintenance, and combat troops. This book examines the ethical implications involved in the widespread use of PMCs, and in particular questions whether they can fit within customary ways of understanding the ethical prosecution of warfare.